Caracterização do aço inoxidável ASTM A743 CA6NM e do seu revestimento de WC-10Co-4Cr aspergido termicamente por HVOF - Martins, André Fernandes [UNESP] (2015)
The high velocity oxygen fuel (HVOF) coating technology, have shown the best results comparing with the related cost and it is able to be spray several coating composition. Due to all these reasons, this is the most used coating process on hydro power plants blades, as it is the case of Santo Antonio project settled in the Madeira river, Rondônia/Brazil. In This research was carried out the martensitic stainless steel characterization ASTM A743 CA6NM, as well as the characterization of the WC-10Co-4Cr coating during the HVOF process. Measurements of roughness, coefficient of friction, hardness, wettability, porosity, coating thickness and microstructure of base metal and coating, by optical microscope, were carried out. These analysis was done on machined stainless steel surface, on blasted surface and on 0,1 and 0,2 mm coating surfaces. The results demonstrate an increase in hardness from 318HV in the stainless steel to 1100HV in the coating. The initial coefficient of friction was 0,2 and raised up to 0,4 after 500 laps on the stainless steel and 0,8 on the coating. The hydrophilic behavior was kept on stainless steel and coating. The coating porosity was below 2% and the Ra roughness around 4,6 Qm